2020
DOI: 10.1021/acs.jpcb.0c01796
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Local Nanostructure of the Aqueous Solutions of the Biocompatible [Cho][Gly] Ionic Liquid: Importance of Hydrogen Bond Attraction between Like-Charged Ions

Abstract: The neat and aqueous solutions of the cholinium glycinate ionic liquid (IL), [Cho]­[Gly], at different water mole fractions, x ws, are studied by molecular dynamics simulations. The changes in the local nanostructure of systems with composition have been determined by calculation of various structural distribution functions. Hydrogen bond (H-bond) attractions determine the major relative orientations of the oppositely and like charged nearest neighbors. The cation–anion H-bonds mainly form between the hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…This apparent contradiction is resolved by the SDFs in Figure D, which show that the probability surfaces for these interactions overlap. This is in agreement with a recent molecular dynamics study on the aqueous solutions of [Ch]­[Gly], in which the authors describe an overall increased repeat spacing between cation–cation, cation–anion, and anion–anion upon the addition of water, while the first peak position of hydrogen bonding between the species remain unchanged …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This apparent contradiction is resolved by the SDFs in Figure D, which show that the probability surfaces for these interactions overlap. This is in agreement with a recent molecular dynamics study on the aqueous solutions of [Ch]­[Gly], in which the authors describe an overall increased repeat spacing between cation–cation, cation–anion, and anion–anion upon the addition of water, while the first peak position of hydrogen bonding between the species remain unchanged …”
Section: Resultssupporting
confidence: 92%
“…This is in agreement with a recent molecular dynamics study on the aqueous solutions of [Ch][Gly], in which the authors describe an overall increased repeat spacing between cation−cation, cation−anion, and anion−anion upon the addition of water, while the first peak position of hydrogen bonding between the species remain unchanged. 28 RDFs between anion groups (guanidine−guanidine and guanidine−carboxylate), in Figure 5B, reveal weak correlations. The guanidine−carboxylate RDF has a peak at 2.2 Å, but the corresponding coordination numbers of 0.04−0.05 are low.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Le Donne et al ( , 2019 using AIMD have found a rough but evident correlation between the association energies of the dimeric anion-anion structures and the measured viscosities of the corresponding ChAAILs. A recent work by Khorrami and Kowsari (2020) based on classical MD has further extended the study of these like-charge interactions to the mixtures of ChAAILs with water.…”
Section: Structure and Computational Studiesmentioning
confidence: 99%